The Correlation between the Use of Social Media and Academic Writing Mastery of the English Education Students - Rizky T Sari; Rita Hayati; Lingga A Suganda (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2019)
The objectives of this study were to find out: (1) the social media which is the most frequently used by the English Education Study Program students, (2) the correlation between the use of social media and academic writing mastery of the students, and (3) the contribution between the use of social media and academic writing mastery of the students. Thirty five students were chosen as the sample by using purposive sampling method. The data were collected through questionnaire and documentation. Pearson Product Moment Correlation Coefficient was used to analyze the obtained data. The result showed that there was a significant correlation between the use of social media and academic writing mastery of students of English education study program (